Structural and Optical Characterizations of Polymethyl Methacrylate Films with the Incorporation of Ultrafine SiO2/TiO2 Composites Utilized as Self-Cleaning Surfaces - Maneerat Songpanit; Kanokthip Boonyarattanakalin; Saksorn Limwichean; Tossaporn Lertvanithphol; Mati Horprathum; Wisanu Pecharapa; Wanichaya Mekprasart (My University, 2023)
The structural and optical characterizations of nanocomposite films of polymethyl methacrylate (PMMA) and SiO2/TiO2 composites prepared via the spin-coating technique were investigated using different SiO2:TiO2 ratios. The SiO2/TiO2 nanocomposites were synthesized using the sonochemical process with Si:Ti precursor ratios of 1:0.1, 1:0.5, 1:1, 1:2, 1:4, and 0:1. All characterizations of ultrafine SiO2/TiO2 particles were loaded at 1 wt.% in a PMMA matrix for the fabrication of transparent SiO2/TiO2/PMMA composite films. The phase structure and morphology of SiO2/TiO2/PMMA composite films were monitored using X-ray diffraction, optical microscopy, and field-emission scanning electron microscopy. A surface roughness analysis of SiO2/TiO2/PMMA nanocomposite films was conducted using atomic force microscopy. For optical characterization, transmission properties with different incident angles of SiO2/TiO2/PMMA composite films were analyzed with UV-vis spectrophotometry. The water contact angles of SiO2/TiO2/PMMA composite films were analyzed to identify hydrophilic properties on film surfaces. Photocatalytic reactions in SiO2TiO2 composite films under UV irradiation were evaluated using rhodamine B dye degradation. The optimal condition of SiO2/TiO2/PMMA nanocomposite films was obtained at a 1:1 SiO2:TiO2 ratio in self-cleaning applications, resulting from good particle dispersion and the presence of the TiO2 phase in the composite.
Keywords: TiO2 Photocatalysis and Solar Cells